2021
DOI: 10.3390/jcm10112418
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Retinal Microsecond Pulse Laser Treatment in Central Serous Chorioretinopathy: A Short-Term Optical Coherence Tomography Angiography Study

Abstract: Background: Central serous chorioretinopathy (CSC) is a common macular condition characterized by detachment of the neuroretina and is a frequent cause of central vision loss in adults. Among the various therapeutic strategies, subthreshold microsecond pulsed laser (SML) treatment has become a useful option. Despite the suggested involvement of choroidal circulatory disturbances in CSC, the effects of this treatment on macular microperfusion have not been fully evaluated yet. Herein, we report the impact of SM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
1
5
0
2
Order By: Relevance
“…Decreased SFCT was noticed after different treatments for CSCR [ 28 31 ]. Similar alterations of choroid thickness after SML treatment were also reported by other researchers [ 21 , 22 ]. Compared with observation, choroidal thickness was significantly lower in the SML-treated group at eight weeks, sixteen weeks, and six months after treatment in acute CSCR [ 15 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Decreased SFCT was noticed after different treatments for CSCR [ 28 31 ]. Similar alterations of choroid thickness after SML treatment were also reported by other researchers [ 21 , 22 ]. Compared with observation, choroidal thickness was significantly lower in the SML-treated group at eight weeks, sixteen weeks, and six months after treatment in acute CSCR [ 15 ].…”
Section: Discussionsupporting
confidence: 90%
“…Arsan et al demonstrated SML could significantly increase BCVA and decrease SRF in non-resolving CSCR patients [ 21 ]. Prasuhn et al showed decreased central retinal thickness after SML in CSCR patients with persistent SRF either with or without secondary CNV [ 22 ]. However, compared with half-dose PDT, SML has a lower SRF complete resolution rate [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…As described above, sublethal RPE hyperthermia has already been clinically proven to be effective in the treatment of several macular diseases such as CSC [5][6][7][8] and DME [9][10][11][12], and this applies to both MP [6,8,11] and CW [32]. Basic experiments have shown an increase in heat shock proteins [34] and subsequent various protective and anti-oxidative stress responses [35], the secretion of cytokines from RPE cells that may lead to improved retinal function [36] and the reduction of the thickness of Bruch's membrane, suggesting inducing elimination of locally accumulated lipids [37].…”
Section: Biological Effects Cw and Mpmentioning
confidence: 99%
“…The micropulse system applies repetitive microsecond pulses (MP) with breaks in between and claims to provide a milder temperature increase at and around the retinal pigment epithelium (RPE) than CW irradiation [4]. In fact, the MP mode has been shown to be effective in the treatment of different macular diseases such as central serous chorioretinopathy (CSC) [5][6][7][8] and diabetic macular edema (DME) [9][10][11][12]. However, a universal understanding of the correct mechanisms of action has not been achieved yet and controversial discussions continue.…”
Section: Introductionmentioning
confidence: 99%
“…These laser therapies induce a sublethal temperature increase in RPE cells, leaving neuroretina intact. SDM, SML and NRT have shown a beneficial effect on a variety of diseases, such as macular edema in diabetic retinopathy [ 30 ] and central serous chorioretinopathy [ 29 ]. Dosing of power remains an unsolved safety issue, especially since the intended region of treatment is the macula.…”
Section: Introductionmentioning
confidence: 99%